2008
DOI: 10.1007/s10562-008-9462-0
|View full text |Cite
|
Sign up to set email alerts
|

The Oxidative Bromination of Methane Over Rh/SiO2 Catalyst

Abstract: Methyl bromide was synthesized by reacting methane with oxygen and hydrogen bromide over Rh/SiO 2 catalyst. The reaction started from the oxidation of HBr to form active bromine species (Br • radicals and Br* surface species), which in turn reacted with CH 4 to form CH 3 • radicals and CH Ã 3 surface species. These CH 3 • and CH Ã 3 species reacted with the active bromine species to form CH 3 Br and CH 2 Br 2 . The presence of HBr inhibited the deep oxidation and the steam reformation of CH 4 and therefore, gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 7 publications
0
7
1
Order By: Relevance
“…In view of halogen corrosion, methane oxidative bromination [5][6][7][8] and chlorination [9] were studied which use hydrobromic acid or HCl as reactants instead of halogens to reduce corrosion problem. Zhou et al [5,6,10] firstly reported methane oxidative bromination (OBM) reaction and developed Ru-and Rh-containing catalysts which showed high selectivity for CH 3 Br and excellent stability, but the uses of noble metals raise the production cost. We also reported FePO 4 /SiO 2 [8] for the OBM reaction, producing nearly equal-molar CH 3 Br and CO which could be used as feed stock for producing acetic acid.…”
Section: Introductionmentioning
confidence: 99%
“…In view of halogen corrosion, methane oxidative bromination [5][6][7][8] and chlorination [9] were studied which use hydrobromic acid or HCl as reactants instead of halogens to reduce corrosion problem. Zhou et al [5,6,10] firstly reported methane oxidative bromination (OBM) reaction and developed Ru-and Rh-containing catalysts which showed high selectivity for CH 3 Br and excellent stability, but the uses of noble metals raise the production cost. We also reported FePO 4 /SiO 2 [8] for the OBM reaction, producing nearly equal-molar CH 3 Br and CO which could be used as feed stock for producing acetic acid.…”
Section: Introductionmentioning
confidence: 99%
“…However, the integration of the alkane functionalization with the HBr recovery in a single step process via oxybromination reaction (Fig. 1, bottom left) is conceptually a more advanced strategy, as it enables process intensification and a theoretical 100% halogen atom efficiency [15][16][17][18][19] . In fact, the oxyhalogenation of light alkanes, which has a long history dating back to the first half of the 20 th century 20 , has been forecasted as the most cost-effective technology for natural-gas upgrading 1 .…”
mentioning
confidence: 99%
“…For the Rh/SiO 2 catalyst, methyl bromide was successfully produced from methane, oxygen, and hydrogen bromide [55]. The active bromine species were Br • radicals and Br surface species, which were formed by HBr oxidation.…”
Section: Oxidative Catalytic Halogenationmentioning
confidence: 99%